In vitro antibacterial activity of Vernonia amygdalin a leaves extracts against pathogen of heart rot disease - Abdul Aziz, Noorshilawati; Mazlan, Hamimah; Abdullah, Nor Suraya; Omar, Muhammad Nor (2016)
Heart rot disease is one of the major diseases in pineapple cultivation in Malaysia. Josapine and N36 are among varieties that vulnerable to the heart rot disease. The infection can reduce up to 50% yield. In vitro antibacterial activity of four Vernonia amygdalina leaves extract (hexane, chloroform, methanol and aqueous) was carried out and evaluated against pathogen of heart rot disease. The antibacterial activity was evaluated using well diffusion method where three concentrations for each extracts were prepared. The results revealed that Vernonia amygdalina chloroform and aqueous leaves extracts at 10000ppm shows greater inhibition zone than positive control. Vernonia amygdalina hexane leaves extracts however did not shows any inhibition zone at any concentrations. Meanwhile, the Vernonia amygdalina methanol leaves extract shows antibacterial activity against pathogen of heart rot disease but not as good as positive control. Phytochemical screening was also carried out to determine alkaloid, flavanoid, glycoside, phenol, saponin, steroid, and tannins as these compounds may attribute to the result. The screening revealed that both Vernonia amygdalina chloroform and aqueous leaves extracts contain alkaloid, saponin, and tannin. Result shows the potentials of Vernonia amygdalina as antibacterial agent in combating plant disease infections.